(untitled) (Research, Society and Development, 2022)
The presence of an underlying lung disease in pregnant women can present as a challenging case. The Vanishing Lung Syndrome is considered a rare condition, in which pulmonary emphysema is usually observed. We describe a unique case of Vanishing Lung Syndrome in pregnant patient. Female patient, 29 years old, started having progressive dyspnea on exertion in 2019, without other associated symptoms. She was hospitalized and a chest imaging study showed the presence of a large bulla in the upper right hemithorax with “hypertensive” behavior. The patient was lost to follow-up and returned two years later, pregnant, with a gestational age of 17 weeks, with an important restrictive component described in the spirometry. A bullectomy and right middle lobectomy were performed, and the patient showed significant symptom and pulmonary evaluation improvement. There are no documented cases of this rare condition in a pregnant patient, with an emphasis on seeking to maintain maternal and fetal well-being. The management of Vanishing Lung Syndrome in pregnant women is challenging, especially when lung function is impaired, as in the described case.